Books recommended by Ethos - CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2024)
Propozycje "Ethosu. Kwartalnika Instytutu Jana Pawła II KUL": Michiko Kakutani, The Great Wave: The Era of Radical Disruption and the Rise of the Outsider, New York: Crown, 2024